2020
DOI: 10.3390/ijms21020422
|View full text |Cite
|
Sign up to set email alerts
|

Light Pollution Changes the Toxicological Effects of Cadmium on Microbial Community Structure and Function Associated with Leaf Litter Decomposition

Abstract: Artificial light at night (ALAN/A) can not only alter the behavior and communication of biological organisms, it can also interact with other stressors. Despite its widespread use and the numerous potential ecological effects, little is known about the impact of ALAN on plant litter decomposition under cadmium (Cd) pollution in aquatic ecosystems. In an indoor microcosm experiment, we tested single and combined effects of ALAN and Cd on the activities and community structure of fungi associated with plant litt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 41 publications
0
9
0
1
Order By: Relevance
“…Otros problemas que origina la intensidad de luz urbana o suburbana incluyen el cambio de color en las hojas de árboles, retención prolongada en especies de hoja caduca, floración y brotación a destiempo, crecimiento o defensa contra patógenos (Falcón et al, 2020). En el caso de los hongos, Liu et al (2020) investigaron los efectos interactivos entre ALAN y la capacidad de la comunidad fúngica para descomponer la basura acuática, encontrando que ALAN inhibe la capacidad de descomposición de la comunidad fúngica.…”
Section: Intensidad De Luzunclassified
“…Otros problemas que origina la intensidad de luz urbana o suburbana incluyen el cambio de color en las hojas de árboles, retención prolongada en especies de hoja caduca, floración y brotación a destiempo, crecimiento o defensa contra patógenos (Falcón et al, 2020). En el caso de los hongos, Liu et al (2020) investigaron los efectos interactivos entre ALAN y la capacidad de la comunidad fúngica para descomponer la basura acuática, encontrando que ALAN inhibe la capacidad de descomposición de la comunidad fúngica.…”
Section: Intensidad De Luzunclassified
“…A total of 216 studies were identified. These studies included behavioral and physiological responses in plants [59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77]; arthropods, including insects and spiders [71,; fish ; amphibians [148][149][150][151][152][153][154][155][156][157][158][159]; reptiles [160][161][162][163][164][165][166][167]; birds ; and non-human mammals, including bats, primates, rodents, and marsupials [24,160,161,174,, when their habitats, aquatic or terrestrial, were artificially illuminated with direct or indirect emissions of ALAN (i.e., all light sources of artificial light). The results of our systematic review show that the most studied organism groups exposed to night-time illumination were birds (76 studies); arthropods, insects and spiders (43 studies); non-human mammals, including bats, primates, rodents, and marsupials (30...…”
Section: Impact Of Artificial Lighting On Organism Groupsmentioning
confidence: 99%
“…In addition, ALAN was shown as a disruptor of processes that can even affect interactions between plants and other organisms. For instance, plants exposed to ALAN demonstrated an earlier initiation of budburst [63], an early and increased flowering process [60,64,65], a delayed flowering state [66], altered plant-herbivore interactions [67,68], altered leaf litter decomposition [69,70], and disrupted pollen transport [68].…”
Section: Plantsmentioning
confidence: 99%
“…The described effects of night lighting (including by LEDs) include tree leaf colouring, retention/abscission (on deciduous trees), budding, flowering, growth, or defence against pathogens. In the case of fungi involved in litter decomposition of streams, and which play a key role in the carbon and nutrient dynamics of stream ecosystems, ALAN can alter community structure and composition, resulting in inhibition of litter decomposition ( Liu et al, 2020 ).…”
Section: Impact Of Alan and Leds On Living Organismsmentioning
confidence: 99%